Manufacturing process transfer to a 30 kg/h continuous direct compression line with real-time composition monitoring - Waněk, Adam; Menarini, Lorenzo; Giatti, Federica; Kubelka, Tomáš; Consoli, Fabrizio; Funaro, Caterina; Stasiak, Pawel; Štěpánek, František (International journal of pharmaceutics, 2024)
Transferring an existing marketed pharmaceutical product from batch to continuous manufacturing (CM) without changes in regulatory registration is a challenging task in the pharmaceutical industry. Continuous manufacturing can provide an increased production rate and better equipment utilisation while retaining key quality attributes of the final product. Continuous manufacturing necessitates the monitoring of critical quality attributes in real time by appropriate process analytical tools such as near infra-red (NIR) probes. The present work reports a successful transfer of an existing drug product from batch to continuous manufacturing process without changing the formulation. A key step was continuous powder blending, whose design and operating parameters including weir type, agitation rate, dynamic hold-up and residence time were systematically investigated with respect to process repeatability. A NIR-based multivariate data model for in-line composition monitoring has been developed and validated against an existing quality control method for measuring tablet content uniformity. A continuous manufacturing long-run with a throughput of 30 kg/h (approx. 128,000 tablets per hour), uninterrupted for 320 min, has been performed to test and validate the multivariate data model as well as the batch to continuous process transfer. The final disintegration and dissolution properties of tablets manufactured by the continuous process were found to be equivalent to those manufactured by the original batch process.
Keywords: farmaceutická chemie; prášky, zásypy, pudry; Powders; řízení kvality; Spectroscopy, Near-Infrared; blízká infračervená spektroskopie; Chemistry, Pharmaceutical; pomocné látky; Solubility; Drug Liberation; tablety; rozpustnost; farmaceutická technologie; příprava léků; Quality Control; Excipients; Drug Compounding; uvolňování léčiv; Tablets; Technology, Pharmaceutical